FORMULATION AND DEVELOPMENT OF MUCOADHESIVE TABLETS OF CAPTOPRIL - Ganesh Kumar Gudas; D.V.R.N. Bhikshapathi (International Journal of Pharmacy and Analytical Research, 2015)
The development of mucoadhesive tablets of captopril which were designed to prolong the gastric residence time after oral administration. Matrix tablets of captopril were formulated using different mucoadhesive polymers such as carbopol 940 p, hydroxyl propyl methyl cellulose (HPMC) K45M, SCMC, RH (Relative Humidity) in various ratios for treatment of hypertension. Currently hypertension has become a common problem in all over the world, due to effectiveness and intensive use of captopril as a drug of choice in the treatment of hypertension and congestive heart failure, development of oral controlled release dosage form of captopril has been an interested topic of research for a long period of time. The tablets were evaluated for various parameters such as compatibility studies, drug content, weight variation, hardness, thickness, friability, swelling studies, in vitro drug release studies, in vitro mucoadhesion strength ,ex vivo residence time test and release rate kinetics. The in vitro release kinetics studies reveal that all formulations fits well with zero order, followed by korsmeyer-peppas, higuchi and the mechanism of drug release is erosion. After analysis of different evaluation parameters and drug release kinetics, formulation code f12 was selected as a promising formulation for delivery of captopril as a mucoadhesive gastroretentive tablet with best mucoadhesive strength and 96.68% drug release at 12th hour. Stability studies of the selected formulation was carried out to determine the effect of formulation additives on the stability of the drug and also to determine the physical stability of the formulation. The stability studies were carried out at 40°c/75% rh for 90days. There was no significant change in the physical property and weight variation, hardness, thickness, friability, in vitro drug release studies, in vitro mucoadhesion strength drug content during the study period.